Development of the Entrepreneurship Program Implementation Strategy for Elementary School Students - Apriyanto, Ridwan Eko; Suyud, Suyud; Pujaningsih, Pujaningsih (Jurnal Prima Edukasia, 2024)
The entrepreneurship program in Indonesia is a manifestation of the initiative to enhance the image of Pancasila students. However, there are still areas that need improvement in the implementation, and there is a lack of research on the strategies for developing entrepreneurship programs. Therefore, it is crucial to develop a strategy to assist in the execution of the entrepreneurship program. This study employed a qualitative approach, specifically utilizing a case study design. Data was gathered by conducting interviews with three individuals who played a crucial role in the entrepreneurship program at Muhammadiyah Prambanan Elementary School. The findings indicate that schools incorporated entrepreneurship into their curriculum through various means, such as organizing field trips, setting up food stands, and hosting artwork exhibitions. The approach to developing the implementation of the entrepreneurship program involved the formation of committees, establishing partnerships with external schools, and engaging work instructors. Factors that contributed to the research included strong support from stakeholders and external schools through collaboration, while obstacles emerged from a lack of skills among existing school staff and challenges with guardians/parents. This study offers a comprehensive analysis of the approach to establishing entrepreneurship programs in educational institutions. It aims to provide valuable insights for other schools seeking to develop similar initiatives.